1979
DOI: 10.3109/00365527909179890
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a β2-Sympathomimetic on Histamine-stimulated Gastric Acid Secretion in Dogs

Abstract: The effect of a selective beta2-adrenoceptor agonist on histamine-stimulated gastric acid secretion was studied in conscious gastric-fistula dogs. A dose-dependent inhibition was found, most pronounced for the lowest doses of histamine. The inhibition was on the volume, whereas the acidity was unchanged. The pulse rate was increased by the beta2-agonist and by histamine. Propranolol prevented the inhibition of acid secretion as well as the increase in pulse rate. Practolol had no effect on the inhibition of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In that respect, it is of interest to notice the opposite effects of catecholamines observed in laboratory animals in vitro and in vivo, even within the same species [31-351. For example, Gottrup et al showed that injections of beta agonists decrease gastrin-induced, and to a lesser extent, basal and histamine-induced acid secretion in dogs [31,32,331. Similar inhibitory effects of catecholamines were observed by Canfield et al in rat ir!…”
Section: Discussionmentioning
confidence: 99%
“…In that respect, it is of interest to notice the opposite effects of catecholamines observed in laboratory animals in vitro and in vivo, even within the same species [31-351. For example, Gottrup et al showed that injections of beta agonists decrease gastrin-induced, and to a lesser extent, basal and histamine-induced acid secretion in dogs [31,32,331. Similar inhibitory effects of catecholamines were observed by Canfield et al in rat ir!…”
Section: Discussionmentioning
confidence: 99%